1985
DOI: 10.1021/ic00216a039
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectroscopic properties of ethynylsulfur pentafluoride (SF5C.tplbond.CH)

Abstract: 3668an increase in the energy of ligand field states, this nonproductive deactivation channel is removed and the efficiency of photosensitization is greatly increased.Inorg. Chem. 1985, 24, 3668-3670 are currently attempting to grow large single crystals of PBC in order to study the photoconductivity and other electrical properties of this material.--Using these two criteria, it should be possible to design many Magnus-type materials that will be photoactive. Whether photoactivity is merely a result of ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The J SF5-CH cis coupling values are near 0 or absent for SF 5 CH¼CH 2 [17], SF 5 CBr¼ CHCl [19], SF 5 CH¼CHCl [18], SF 5 CH¼CHOCH 3 [18], SF 5 CBr¼CHBr [20], SF 5 CCl¼CH 2 [21] and SF 5 CBr¼ CHCl [16]. Also of interest is the J SF5-CH trans interaction; for SF 5 CH¼CH 2 [17], SF 5 CH¼CHOCH 3 [18], SF 5 CBr¼ CHBr [20], and SF 5 CCl¼CH 2 [21], and trans-SF 5 CBr¼CHCl [19] the coupling values are 2.3, 3, 3.0, 3.3 and 2.2 Hz, respectively. It is clear from our data that all new compounds (1-3) have SF 5 CH¼ arrangement based on the values for the geminal coupling.…”
Section: Resultsmentioning
confidence: 94%
“…The J SF5-CH cis coupling values are near 0 or absent for SF 5 CH¼CH 2 [17], SF 5 CBr¼ CHCl [19], SF 5 CH¼CHCl [18], SF 5 CH¼CHOCH 3 [18], SF 5 CBr¼CHBr [20], SF 5 CCl¼CH 2 [21] and SF 5 CBr¼ CHCl [16]. Also of interest is the J SF5-CH trans interaction; for SF 5 CH¼CH 2 [17], SF 5 CH¼CHOCH 3 [18], SF 5 CBr¼ CHBr [20], and SF 5 CCl¼CH 2 [21], and trans-SF 5 CBr¼CHCl [19] the coupling values are 2.3, 3, 3.0, 3.3 and 2.2 Hz, respectively. It is clear from our data that all new compounds (1-3) have SF 5 CH¼ arrangement based on the values for the geminal coupling.…”
Section: Resultsmentioning
confidence: 94%
“…The reaction of SF 5 Br with acetylene also produces SF 5 CH CHBr and is an alternative method for preparing this compound [8]. The new method presented in this paper (see Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In the 'H nmr spectra of the acids and their salts, it is observed that the chemical shifts of the protons are in the region expected for SF5 hydrocarbons; the protons are found in the -4-7 ppm range (4,5). In three cases the couplings of the equatorial fluorines (SF4) and the couplings of the aliphatic fluorines to the a protons could be determined; for the rest a complex multiplet was observed.…”
Section: Resultsmentioning
confidence: 92%